Euphorbia hirta L. a new host record of Oidium species from Nepal - Adhikari, Mahesh Kumar (Nepal Journal of Science and Technology, 2021)
Euphorbia hirta L. which was found parasitized by the Oidium species (imperfect stage of Erysiphales), on the leaves, is considered as a new host record for the fungus. It was collected in the promises of Nepal Academy of Science and Technology (NAST), Khumaltar, Nepal. The description of the fungus and distribution is provided here with.